Dosimetric impact of intrafraction motion on boosts on intraprostatic lesions: a simulation based on actual motion data from real time ultrasound tracking - Ballhausen, Hendrik (Radiat Oncol, 2019)
BACKGROUND: Intrafraction motion is particularly problematic in case of small target volumes and narrow margins. Here we simulate the dose coverage of intraprostatic lesions (IPL) by simultaneous integrated boosts (SIB). For this purpose, we use a large sample of actual intrafraction motion data. METHODS: Fifty-three h of intra-fraction motion of the prostate were recorded in real-time by 4D ultrasound (4DUS) during 720 fractions in 28 patients. We simulate spherical IPLs with 3, 5, and 7 mm radius and matching spherical SIBs with 0, 2, and 5 mm safety margins. The volumetric overlap between IPLs and SIBs is calculated. Dose volume histograms (DVH) are estimated by Monte Carlo simulation. RESULTS: On average, the distance of the prostate was 1.3 mm from its initial position over all fractions and patients. Average volumetric overlap was 73, 82, and 87% of IPL volume in case of 3, 5, and 7 mm IPLs and SIBs without safety margins. These improved to 95% or more in case of 2 mm safety margins and 98% or more in case of 5 mm safety margins. DVHs showed that 80% of the IPL volume received 60, 72, and 79% of maximum dose in case of 3, 5, and 7 mm IPLs and SIBs without safety margins. These improved to 94% or more given moderately sized safety margins of 2 mm. CONCLUSIONS: On average over all fractions and patients, the dose coverage would have been acceptable even for small target volumes such as IPLs of radius 3 to 7 mm and narrow fields. Moderate safety margins of 2 mm could have ensured a delivery of 90% or more of the SIB dose to the IPL. In this case, SIB volume would have been considerably larger than IPL volume, but still considerably smaller than the overall PTV of the prostate. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13014-019-1285-1) contains supplementary material, which is available to authorized users.